2007
DOI: 10.1007/s10661-006-9435-y
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Heavy Metals in Water from Boreholes in Dumasi in the Wassa West District of Western Region of Republic of Ghana

Abstract: Concentrations of heavy metals in the borehole at Dumasi in the Wassa West District of the Republic of Ghana have been measured in this study. The concentrations of the following metals in the ground water from Dumasi borehole are: Iron (Fe) - 7.52 ppm, Manganese (Mn) - 1.11 ppm, Arsenic (As) - 4.52 ppm, Chromium (Cr) - 0.026 ppm, Cobalt (Co) - 0.01 ppm, Zinc (Zn) - 0.007 ppm, Cadmium (Cd) - 0.002 ppm and Lead (Pb) - 0.005 ppm. The results of the study show that resident adults and children who use water from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 3 publications
1
49
3
Order By: Relevance
“…Case studies from the country's gold mining areas cite severe environmental impacts including trace element contamination of soils, water and food (Amonoo-Neizer et al 1996;Smedley et al 1996;Armah et al 1998;Smedley and Kinniburgh 2002;Aryee et al 2003;Babut et al 2003;Andur and Norman 2005;Obiri et al 2006;Essumang et al 2007;Obiri 2007). There is, therefore, a need for regular monitoring of the mining ecosystems in Ghana to ensure early detection of pollution and to institute measures to mitigate the potential health risks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case studies from the country's gold mining areas cite severe environmental impacts including trace element contamination of soils, water and food (Amonoo-Neizer et al 1996;Smedley et al 1996;Armah et al 1998;Smedley and Kinniburgh 2002;Aryee et al 2003;Babut et al 2003;Andur and Norman 2005;Obiri et al 2006;Essumang et al 2007;Obiri 2007). There is, therefore, a need for regular monitoring of the mining ecosystems in Ghana to ensure early detection of pollution and to institute measures to mitigate the potential health risks.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on environmental impacts of mining in Ghana (most of which centred around the Ashanti Goldfields Mine at Obuasi) focused mainly on arsenic and mercury contamination (Amonoo-Neizer and Amekor 1993;Amonoo-Neizer et al 1996;Hilson 2002;Oberthur et al 1997;Smedley 1996;Smedley and Kinniburgh 2002;Smedley et al 1996). A few studies around Tarkwa, Bogosu and Prestea, on the other hand, targeted only arsenic concentrations in water (Asante et al 2006;Obiri 2007;Serfor-Armah et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This is the process of estimating the health effects that might result from exposure to carcinogenic and non-carcinogenic chemicals (Obiri et al, 2007;Artiola et al, 2004;USEPA, 2001). In this study, non-carcinogenic health risk refers to harm done to the central nervous and other adverse health effects (except cancer) due to exposure to neurotoxic chemicals such as Hg and Pb.…”
Section: Health Risk Assessment Processmentioning
confidence: 99%
“…Hg is found in soils and rocks typically as an ore known as cinnabar, consisting of insoluble mercuric sulphide. In Ghana, the presence of Hg in the environment is attributed to the use of Hg in gold recovery processes where the inorganic Borehole 3 form of the metal either is washed into rivers or is vaporized readily into the atmosphere (Obiri, 2005;2007;Chapman, 1996). From Table 3, it was observed that Hg had a weak correlation with other trace metals measured during the study, implying that they seem not to emanate from the same source.…”
Section: Concentration Of Hg CD As Cu and Pbmentioning
confidence: 99%
“…This is the process of estimating the health effects that might result from exposure to carcinogenic and non-carcinogenic chemicals [17][18][19]. In this study, non-carcinogenic health risk refers to harm done to the central nervous and other adverse health effects (except cancer) due to exposure to neurotoxic chemicals such as Hg and Pb.…”
Section: Health Risk Assessment Processmentioning
confidence: 99%